Cognitive problem-solving abilities and speech acts in children: an analysis in vulnerable family contexts - Morelato, Gabriela Susana (2015)
The goal of this study was to analyze the cognitive abilities involved in interpersonal problemsolving and their connection with speech acts in children from contexts of social vulnerability. The sample included 120 schoolchildren between the ages of 8-13 in Mendoza, Argentina. The results showed that the children from more vulnerable family backgrounds, presented significantly less expressive speech acts than children at low vulnerability. It was also observed that displayed significantly poorer identification of emotions and anticipated significantly more negative consequences. In contrast, children who had high level of protective factors identified significantly more emotions, tended to generate more alternatives and anticipated less negative consequences. These results highlight the importance of carrying out early evaluations in contexts of risk, taking a preventive approach, and articulating knowledge from the fields of psychology and linguistics in order to develop new kinds of intervention and support strategies destined to children in school contexts.